Process improvement on the production of microfibrillated cellulose using fungal pretreatment and ultrasonication - Jimat, Dzun Noraini; Avicenna, Avicenna (2015)
Microfibrillated cellulose (MFC) can be used as rheology modifiers in foods, paints, cosmetics and pharmaceutical products as well as fillers in composite materials. It can be isolated from different lignocellulosic materials using different technologies. In this study, MFC was produced from the substrate of cocoa pod husk (CPH) in two distinct processes. Substrate was subjected to fungal-pretreatment at the first stage through a solid state fermentation by Aspergillus niger to promote enzymatic splitting of cellulose. The obtained fungal pretreated substrate was then mechanically processed by the application of high-intensity ultrasonication. The objective of the research was to define the potential and the optimum process of the fungal pretreatment stage through a response surface design (RSM) with substrate raw particle size (RPS) and inoculums size (IS) as independent variables. Statistical result of RSM showed that the model follows a quadratic response with IS as significant term. The 3D model graph exhibit an inverted peak response surface with maximum particle size of MFC at 2,761 nm at RPH of 850 micron and 5.0 % IS. Results from SEM images showed that the structure and morphology of the resulted MFC differed over the various level of IS with approximated diameter of MFC at 30 – 50 micron. Fungal-pretreatment also proven to remove amorphous structure of hemicelluloses and lignin giving a loosen structure that appeared to be at the size of about 50 µm to certain hundreds micrometer. FTIR results indicated a prominent change of spectra over the stages with a notable peak at the range of 3600 cm-1 and 2600 cm-1 appeared as a vibration of the OH-stretching and CH-stretching. The approximated peak of 1730 cm-1 from the raw substrate indicates the presence of hemicellulose, where at the later samples of the fungal pretreated substrate, the spectra showed a lower intensity, and mostly disappeared after the process of ultrasonication.